A Continuous, High-Frequency Environmental Monitoring System for Watershed Education Research - Mcdonald, Walter M.; Lohani, Vinod K.; Dymond, Randel L.; Brogan, Daniel S. (Journal of Engineering Education Transformations, 2015)
The Learning Enhanced Watershed Assessment System (LEWAS) is an environmental monitoring lab on the Virginia Tech, USA campus that uses contemporary sensing and computing technologies to provide high-frequency (1-3 minute sampling intervals) continuous water and weather data from a small urban watershed (2.78 km2) in order to promote watershed research and education. The LEWAS integrates custom software applications with data collection hardware, environmental sensors, and renewable power to create a remote automated watershed monitoring system. Watershed education research is illustrated through case studies based on LEWAS data that demonstrate the value of continuous flow and water quality data in small urbanized watersheds through the capture and characterization of acute hydrologic and hydro chemical events. Student-centered active learning modules that incorporate LEWAS data and case studies have been successfully implemented into an undergraduate hydrology course at Virginia Tech. Assessment results reveal positive student perceived learning gains from instructional activities that incorporate LEWAS data.